Bemisia tabaci-mediated facilitation in diversity of begomoviruses: Evidence from recent molecular studies. (October 2018) - Islam, Waqar; Akutse, Komivi Senyo; Qasim, Muhammad; Khan, Khalid Ali; Ghramh, Hamed A.; Idrees, Atif; Latif, Shahid
Abstract: Begomoviruses are considered as one of the most notorious plant viruses worldwide, which cause substantial economic losses to various field crops. Management of begomoviruses has become a challenge due to the continuous evolution and the emergence of new strains. Bemisia tabaci is globally known to be the key vector of begomoviruses, having relatively high reproductivity, fast dispersal ability, high survival rate due to its polyphagous nature and high resistance to various groups of insecticides. Continuous transmission of begomoviruses by the vector has led to the development and spread of epidemics of various diseases worldwide. In this review, we have critically analyzed the various dynamics which facilitate the diversity of begomoviruses through their vector. The interaction of begomovirus-whitefly leads to continuous research activities regarding management of both virus and its vector, thus opening exciting new horizons to formulate potential control strategies to ensure a disease-free cropping environment. Highlights: Begomoviruses are considered as one of the most notorious plant viruses. Management of begomoviruses has become a challenge due to the continuous evolution. Bemisia tabaci is globally known to be the key vector of begomoviruses. Continuous transmission of begomoviruses by vector has led to the development and spread of epidemics of various diseases. We have analyzed the various dynamics which facilitate the diversity of begomoviruses through their vector.